VHSV Single Amino Acid Polymorphisms (SAPs) Associated With Virulence in Rainbow Trout - Panzarin, Valentina; Cuenca, Argelia; Gastaldelli, Michele; Alencar, Anna L. F.; Pascoli, Francesco; Morin, Thierry; Blanchard, Yannick; Cabon, Joëlle; Louboutin, Lénaïg; Ryder, David; Abbadi, Miriam; Toffan, Anna; et al. (Frontiers in Microbiology, 2020)
The Viral Haemorrhagic Septicaemia Virus (VHSV) is an OIE notifiable pathogen widespread in the Northern Hemisphere that encompasses four genotypes and nine subtypes. In Europe, subtype Ia impairs predominantly the rainbow trout industry causing severe rates of mortality, while other VHSV genotypes and subtypes affect a number of marine and freshwater species, both farmed and wild. VHSV has repeatedly proved to be able to jump to rainbow trout from the marine reservoir, causing mortality episodes. The molecular mechanisms regulating VHSV virulence and host tropism are not fully understood, mainly due to the scarce availability of complete genome sequences and information on the virulence phenotype. With the scope of identifying in silico molecular markers for VHSV virulence, we generated an extensive dataset of 55 viral genomes and related mortality data obtained from rainbow trout experimental challenges. Using statistical association analyses that combined genetic and mortality data, we found 38 single amino acid polymorphisms scattered throughout the complete coding regions of the viral genome that were putatively involved in virulence of VHSV in trout. Specific amino acid signatures were recognised as being associated with either low or high virulence phenotypes. The phylogenetic analysis of VHSV coding regions supported the evolution towards greater virulence in rainbow trout within subtype Ia, and identified several other subtypes which may be prone to be virulent for this species. This study sheds light on the molecular basis for VHSV virulence, and provides an extensive list of putative virulence markers for their subsequent validation.